Nomos Empsychos towards a Historiography of the Greek Living Law Idea - Tussay Ákos (POLIS: THE JOURNAL FOR ANCIENT GREEK POLITICAL THOUGHT, 2024)
In the Middle Ages, the idea of legislative sovereignty was expressed with reference to a host of commonplace arguments, such as pater legis, Sol Iustitiae , or lex animata . And many believe that it was the Roman legal concept of animate law which eventually laid the foundation for the elaboration of the idea of absolute power in the late Middle Ages. If this hypothesis is correct, the philosophic background of some late medieval and early modern absolutistic doctrines of political government could be sought after as early as the classical Greek descriptions of a king who is nomos empsychos , that is, a living law. In this article, I intend to consider this intellectual tradition, and raise some doubts about the merits of the above claim, arguing instead for a separate consideration of the individual sources of the nomos empsychos concept. As such, I am tracing the genealogy of the expression to the fifth-century Pythagorean, Archytas of Tarentum, and I am demonstrating that originally the nomos empsychos was inseparably associated with an intrinsically Archytean tradition.